(untitled) (Nepal Journal of Epidemiology, 2018)
Background: It has been seen that very less attention has been given to the oral health of the geriatric population residing in old age homes and as the oral mucosal lesions are a matter of concern for this growing population. Therefore, a study was done with the objective of finding the prevalence of oral mucosal lesions and the distribution of oral mucosal lesions among 65-74 year old residents of old age homes in Delhi, India. Materials and Methods: A cross sectional study was done on 65-74 year old age group elders of old age homes in Delhi. A total of 464 subjects participated in the study. Oral Health Assessment Form, WHO was used for assessing oral mucosa. Clinical examination was performed using two mouth mirrors under natural illumination in a systematic manner. Data was processed and analyzed using SPSS version 23. Results: Out of a total of 464 subjects, 291 (62.70%) were males and 173 (37.30%) were females. Oral mucosal lesions seen in the study subjects were malignant tumours, leukoplakia, lichen planus, ulcerations, ANUG, Abscess and candidiasis. Leukoplakia was seen in 70 subjects (15%) and was present on buccal mucosa in the majority. A malignant tumour was seen in 7 subjects (1.5%) and commonly seen area is floor of mouth. Conclusion: Prevalence of oral mucosal lesions among residents of old age homes shows the need for increased preventive and diagnostic measures for prevention and early identification of oro-mucosal lesions. Taking adequate care for oro-mucosal health of elderly people residing in old age homes is necessary.